IMPLEMENTASI PROGRAM PEMBERDAYAAN MASYARAKAT DI BIDANG KEHUTANAN DI KECAMATAN SEBULU KABUPATEN KUTAI KARTANEGARA - Tonny Sopiansyah; Achmad Djumlani; Heryono Susilo Utomo (Jurnal Administrative Reform, 2017)
The purpose of this study is to describe and analyze the implementation of societal empowerment in forestry at Sebulu district Kutai Kartanegara regency as well as factors that hindering it. The result shows that the implantation of the program is still not optimal. One if the main thing influenced the program is the inactivity of local forestry stakeholders in supporting the societal forestry empowerment..